Fronteiras nas obras de Sidônio Apolinário: disputas e negociações de gauleses com itálicos e germânicos (século V e C) - Reis, Gabriel Freitas (2019)
The thematic of the present work concentrates on border conflicts and negotiations established between the Gallo-Roman elite and Germanic confederations present in the region of Gaul of the fifth century CE. We are also dealing with a movement that encompasses Gaulish political crisis and re-significations concerning Roman Republican government centered on Ravenna and controlled by the Italian nobility. For these studies, we used the documentary corpus of a Gallo-Roman author who wrote several works in the fifth century CE, Sidonius Apollinaris. We know that this author was born in Lugdunum (now Lyon, France) between 430/433 and was politically active from the 450s until his death in the 480s. During this time he pursued a political career linked to the court of the Western Roman Empire, which gave him several titles of nobility, including in the ecclesiastical sphere, like bishop of Arverni. The proximity between Sidonius Apollinaris and the Germanic governments established in Gaul of his time, as well as between him and the Roman-Italic imperial government, allowed in his works dense appeared the historical-social relations established between the various elites who sought power in the Gallic territory. Our research, within this framework, intends to analyze the logic of the alliances and agreements established between the Gallo-Roman elite with the objective of perpetuating their power in the sphere of Gaul, when the political-military crises that occurred in Italy prevented the elites of that peninsula protected the Rhine frontiers of the Empire. We try to understand the way cultural identities work for political purposes, such as humanitas. We also want to understand the logic of the networks of amicitia, paying attention to the way they were used according to the needs and interests of Sidonius Apollinaris. We will look at the logic of Christian identities established in Gaul, as well as the way Sidonius Apolinarius used them in search of alliances and maintenance of power and territories, opposing Aryan Christians and Legal Christians. We will try to understand the mechanisms that governed the Sidonian representations and their relations of interest, taking into account the rhetorical elements of the author. In the light of what has been presented, we believe that the work with the Sidonian documentation can collaborate with the understanding of the process of transformation of historical and social elements of its context. In this way, we will insert ourselves in the complex historiographic debate that divides opinions between the existence of a "Fall of the Roman Empire", valuing the ruptures, and between the thinking of the period as a moment of transformations and continuities.